Takojšnji učinki elastičnega lepilnega traku na aktivnost mišice vastus medialis oblikus pri pacientih po vstavitvi kolenske endoproteze po resekciji tumorja - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2016)
Background: After receiving a knee endoprosthesis because of tumor resection in the distal part of femur, the patients have decreased strength of quadriceps muscle. The aim of the study was to determine if kinesio taping increases activity of the vastus medialis obliquus muscle in these patients. Methods: We applied kinesio tape on the vastus medialis obliquus muscle and measured electrical activity with surface electromyography in eight patients (3 male and 5 female). Their average age was 43 years (range 20 to 60 years). We measured average maximal contraction of vastus medialis obliquus muscle at four time points: before kinesio taping, 10 minutes after kinesio taping, after one hour and 24 hours after kinesio taping. Results: We observed statistically significant improvement of vastus medialis obliquus muscle activity. Ten minutes after kinesio taping the mean electrical activity of the muscle was 94.7 $μ$V (range 27.6 - 184.8 $μ$V); after one hour it was 98.7 $μ$V (range 37.5 - 214.4 $μ$V); and 24 hours after kinesio taping it was 118,4 $μ$V (range 40.6 - 257.6 $μ$V). Conclusion: Kinesio taping has an immediate effect on improvement of the vastus medialis obliquus muscle activity. The muscle activity continues to improve 24 hours after kinesio taping application.
Keywords: elastični lepilni trak; Electromyography; kinesio taping; knee endoprosthesis; kolenska endoproteza; mišica vastus medialis oblikus; površinski EMG; surface electromyography; vastus medialis obliquus muscle